2022
DOI: 10.1039/d1cs00891a
|View full text |Cite
|
Sign up to set email alerts
|

Construction and application of base-stable MOFs: a critical review

Abstract: This review focuses on the construction and the application of base-stable MOFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
87
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(104 citation statements)
references
References 228 publications
0
87
0
Order By: Relevance
“…MOFs have attracted tremendous interest in the immobilization of ILs for the synthesis of catalysts, owing to their remarkable advantages, including crystalline frameworks, high specific surface area, ordered pore structure, and uniform adjustable pore size ( Cong et al, 2021 ). Meanwhile, compared with other porous materials, MOFs exhibit uniform porous structures with large specific surface areas, regular and adjustable pore, and versatile architecture ( Wang et al, 2022 ).…”
Section: Ionic Liquid-functionalized Metal–organic Frameworkmentioning
confidence: 99%
“…MOFs have attracted tremendous interest in the immobilization of ILs for the synthesis of catalysts, owing to their remarkable advantages, including crystalline frameworks, high specific surface area, ordered pore structure, and uniform adjustable pore size ( Cong et al, 2021 ). Meanwhile, compared with other porous materials, MOFs exhibit uniform porous structures with large specific surface areas, regular and adjustable pore, and versatile architecture ( Wang et al, 2022 ).…”
Section: Ionic Liquid-functionalized Metal–organic Frameworkmentioning
confidence: 99%
“…12,13 However, most of the ECL studies of BODIPYs have been carried out in organic systems, 14 since their optical properties are strongly restricted by intermolecular π–π stacking interactions. 15,16 In order to overcome the phenomenon, plenty of studies were devoted to the linking of various functional groups on BODIPYs to obtain BODIPY derivatives dispersible in water, thereby increasing the molecular distance and improving their optical or electrochemical properties in the aqueous phase. 17,18 In another case, hydrophobic BODIPYs were introduced into a mixed oil-in-water emulsion composed of toluene and tri- n -propylamine.…”
mentioning
confidence: 99%
“…12 On the other hand, metal−organic frameworks (MOFs), as an emerging subclass of porous hybrids, are self-assembled from inorganic metal centers with versatile organic linkers. 13,14 Multifunctional MOF materials are very appealing as a result of their large porosity, high specific surface area, diversified functionality, and tailorable structural chemistry. 15−17 MOFs have been well demonstrated to be utilized in efficient catalysis when they are combined with external catalysts.…”
mentioning
confidence: 99%
“…On the other hand, metal–organic frameworks (MOFs), as an emerging subclass of porous hybrids, are self-assembled from inorganic metal centers with versatile organic linkers. , Multifunctional MOF materials are very appealing as a result of their large porosity, high specific surface area, diversified functionality, and tailorable structural chemistry. MOFs have been well demonstrated to be utilized in efficient catalysis when they are combined with external catalysts. However, employing microporous MOFs as robust host materials to afford a confined space where the limited growth of ultrafine metal particles can be achieved under certain conditions. , These well-dispersed metal nanoparticles (NPs) precisely encapsulated inside large MOF pores are a potential platform for heterogeneous catalysis with high selectivity. Inspired by this, it is found that MOFs assembled with high-valent metals, such as In­(III) and Zr­(IV), can greatly improve the structural stability in aqueous solutions, which are obviously favorable when employed as a robust host for heterogeneous catalysis.…”
mentioning
confidence: 99%